Analisis Wireless Access Point Pada Wifi Dengan Menggunakan Metode Wardriving Di Kecamatan Tampan Kota Pekanbaru (Studi Kasus: Kecamatan Tampan) - Wijayanto, M. Rido; Sari, Linna Oktaviana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The development of information technology is currently growing with the growth of human needs, wihich require simplicity, speed and security of access to information wireless tetchnolgoyn network rhas now become an important requiretment ofr the general public, userts who are usuallyfacilitated in public places such as: malls, offices, cafes, hotels, airports, hospitals, educational institutions and places of business and business. wireless network make it easy for users to get internet, wifi network are transmitted via radiio wave frequencies, for communication needs, information or data transfer and other purposess. The wirless network is divided into two frequensces two, 2.4 Ghz which consistes of 14 channels, and a frequenscy of 5 Ghz. The emission tha uses the same channel of frequenscy will experience overlapping interference from the emission of the same channel around it. From a number of overlalpping test point using InSSIDer and Vistumbler, the average signal quality can be produced -64,75 dBm, in good signal quality, and decreased by an average of -25, 25 dBm, so that network performance becomes -90 dBm in quality poor signal, and on adjacent channels the resulting average is -56 dBm, idn good signal quality, and decreased by -23,33 dBm average, so that the signal quality performance becomes -80 dBm, inlow signal quality. This has mild overlapping of many adjacent channel beams, the 5 Ghzfrequensicy test has absolutely no effect on many surrounding channels, the performance is inn good condition without any interference from the surrounding WiFi channel, channel usage in the Tampan District area still uses Frequency 2.4 Ghz with 91 % data results compared to 5 Ghz frequency with 9% result fro 1015 WiFi beam point in Tampan District, it is still fairly largeoverlapping interference in hansome sub-disctrict, from the result s of the comparison of the frequencies used. In terms of security used in the TAmpan District area, a lot of WPA2 securty type are used with 87% and the unknown security side is unknown or WEP 12%, and the WPA securityused is only 1%. The security side of the WiFi used in the TAmpan District is still safe. In terms of security used of the WiFi used in the Tampan Distrcit is still safe.Keywords : Wardriving, Sinyal Strength, Interferency, Mapping, Wirless WiFi